Effect of parameters on vermicompost's nitrogen, phosphorus and potassium ratio from spent mushroom substrate - Nur Hizami Syazwan Bin Sabdin (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Vermicomposting is a cheap biotechnology tool to decompose a variety of wastes involving the joint action of earthworms and microorganisms. The objective of this study is to produce vermicompost from spent mushroom substrate (SMS) with cow manure by using the African Night Crawler (ANC) worms. Different ratio of SMS to cow manure including 100:0, 80:20, 70:30, 50:50, 30:70, 20:80, 0:100, and 50:50 with added egg shells were used to study the effects on nitrogen, phosphorus, and potassium (NPK) contents, worm biomass, and vegetable growth. Results showed that the ratio of SMS to cow manure of 0: 100 produced the highest composition of NPK content which is 1.98:0.29:0.53. The reproduction of ANC was the highest in treatment 50:50 which is 416. Observation on the growth of vegetable showed that treatment 0:100 produced the tallest plant compared to other treatments including the plant applied with chemical fertilizer with NPK ratio 15:15:15 and control plant without any fertilizer added. Electrical conductivity (EC) reading was the highest in treatment 0:100 which is 2.59 mS/cm. As a conclusion, all the objectives of this study was achieved and shows that different parameters in treating SMS for vermicomposting affect the NPK contents of vermicompost produced.